2017
DOI: 10.1021/acsomega.7b00808
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Methanol Activation by Different Small Mixed Silicon Clusters Si2M with M = H, Li, Na, Cu, and Ag

Abstract: High-accuracy quantum chemical calculations were carried out to study the mechanisms and catalytic abilities of various mixed silicon species Si 2 M with M = H, Li, Na, Cu, and Ag toward the first step of methanol activation reaction. Standard heats of formation of these small triatomic Si clusters were determined. Potential-energy profiles were constructed using the coupled-cluster theory with extrapolation to complete basis set CCSD(T)/CBS, and CCSD(T)/aug-cc-pVTZ-PP for Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 63 publications
(104 reference statements)
1
15
0
Order By: Relevance
“…Improved geometrical parameters are then reoptimized using the same functional but with the larger correlation consistent aug-cc-pVTZ (denoted hereafter as aVTZ) basis set. The B3LYP functional has been shown to provide energetic data in line with experiment, or high accuracy wave function methods such as the coupled-cluster theory CCSD­(T) in previous investigations for both pure and doped silicon clusters ,, and the reactions of water dimer. , Harmonic vibrational frequency analyses are performed at the same level to confirm the nature of the stationary structures and to evaluate the zero-point correction energies (ZPE). Intrinsic reaction coordinate (IRC) profiles are computed at the B3LYP/aVTZ level to make sure that each transition structure (TS) located is correctly connected with two energy minima.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Improved geometrical parameters are then reoptimized using the same functional but with the larger correlation consistent aug-cc-pVTZ (denoted hereafter as aVTZ) basis set. The B3LYP functional has been shown to provide energetic data in line with experiment, or high accuracy wave function methods such as the coupled-cluster theory CCSD­(T) in previous investigations for both pure and doped silicon clusters ,, and the reactions of water dimer. , Harmonic vibrational frequency analyses are performed at the same level to confirm the nature of the stationary structures and to evaluate the zero-point correction energies (ZPE). Intrinsic reaction coordinate (IRC) profiles are computed at the B3LYP/aVTZ level to make sure that each transition structure (TS) located is correctly connected with two energy minima.…”
Section: Methodsmentioning
confidence: 96%
“…In fact, an appropriate dopant can dramatically change some properties of the resulting doped clusters, namely electronic, chemical, and optical features . Earth-alkaline metals have been suggested to be efficient catalyst in many processes. Our recent studies , also revealed that small earth-alkali mixed silicon clusters Si n M with n = 2,3 and M = Be, Mg, Ca, can be regarded to be promising alternatives for the expensive metal-based catalysts used for methanol dissociation and other dehydrogenation processes of organic compounds. In particular, the energy barriers for the cleavage of O–H bond in the presence of doped Si clusters has been found to be lower than all previously reported values on various types of elemental clusters, metal surfaces, or metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The result obtained are suitable with the previous studies about the decomposition of CH3OH on metal surfaces of Pt, Pd, Co, etc. [14,[16][17][18][19][20]22,24] Therefore, considering the CH3OH adsorbent, the highest catalytic adsorption efficiency belongs to the Pt4 cluster, leading to the formation of M-O bonds.…”
Section: Adsorption Of Ch3oh On Clusters M4mentioning
confidence: 99%
“…[2] Other works relate to the decomposition of methanol and formaldehyde to form hydrogen on Pt/Al2O3, Ru-Pt, Pt3/Ni(1 0 0), Zn/Cu(1 1 1), Pd/Zn(1 1 1), Pt13, Pt7, Pt3Cu4, Cu7, etc. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]32] The O-H cleavage or C-H cleavage occurs first depending on the catalytic material used. For instance, Desai and co-workers examined the adsorption of methanol over Pt(1 1 1) in vacuum and concluded that dehydrogenation pathways starting from the activation of the C-H bond are easier than these of the O-H bond.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 These frameworks, characterized by high thermal stability and large surface area, have found extensive use as catalysts in coupling, cross-coupling, nitration, multi-component, oxidation-reduction, and Diels–Alder reactions. 6–11 Crystalline porous frameworks consist of an inorganic sector comprising metal cations as nuclei and an organic sector serving as ligand connectors. 12,13 These frameworks possess highly active surfaces and offer a wide range of functional groups, enabling the design of highly efficient catalysts.…”
Section: Introductionmentioning
confidence: 99%